用于大肠杆菌检测的适配体纳米比色生物传感器及应用 (2024)
本发明提供了一种适配体纳米比色生物传感器及其应用和产品、大肠杆菌的检测方法，涉及生物检测技术领域。本发明提供的适配体纳米比色生物传感器，包括纳米材料和吸附在纳米材料上的适配体，其中纳米材料具有类过氧化物酶活性，适配体为具有特定核苷酸序列的核酸，能够特异性识别并结合大肠杆菌。本发明的适配体纳米比色生物传感器特异性好，灵敏度高，能够应用于大肠杆菌的检测以及制备诊断脓毒症的产品中。本发明提供的大肠杆菌的检测方法，简单方便，能够快速准确的实现对大肠杆菌的定性定量检测，减少大肠杆菌的检测时间，降低检测成本。 The invention provides an aptamer nano colorimetric biosensor, application and a product thereof, and a detection method of escherichia coli, and relates to the technical field of biological detection. The aptamer nano colorimetric biosensor provided by the invention comprises a nano material and an aptamer adsorbed on the nano material, the nano material has peroxidase-like activity, and the aptamer is nucleic acid with a specific nucleotide sequence and can specifically recognize and bind to escherichia coli. The aptamer nano colorimetric biosensor disclosed by the invention is good in specificity and high in sensitivity, and can be applied to detection of escherichia coli and preparation of products for diagnosing sepsis. The detection method of the escherich